Pengaruh Pemotong Daun terhadap Pertumbuhan Setek Tanaman Lada (Piper nigrum L.) pada Komposisi Media yang Berbeda - Almahdi, Muhammad Ali; Sugiatno, Sugiatno; Rugayah, Rugayah; Susanto, Herry (JURNAL AGROTROPIKA, 2022)
Black pepper plant is generally propagated vegetatively using cuttings. One of the problems in pepper breeding is the high mortality rate due to the transpiration rate. One of the efforts to reduce the rate of transpiration is by cutting leaves and by choosing the right composition of planting media. This study aimed to determine the effect of leaf cutting, planting medium composition, and the interaction between leaf cutting and planting medium composition on the growth of pepper cuttings. The research was conducted in a plastic house in Labuhan Dalam Village, Tanjung Seneng District, Bandar Lampung and at the Plant Science Laboratory, Faculty of Agriculture, University of Lampung, Gedong Meneng Bandar Lampung. from October 2020 to February 2021. The study was arranged in a factorial (5x3) with a completely randomized group design. The first factor was leaf cutting which consists of no cutting, ¼ cutting, ½ cutting, ¾ cutting, and full cutting. the second was the composition of the planting medium, which consists of sand + husk charcoal + manure, sand + manure, and husk charcoal + manure. The results showed that: (1) Treatment full cutting resulted in the fastest shoot emergence, lengthening of shoots, increasing number of leaves, and increasing shoots' fresh and dry weight; (2) the composition of the planting media did not affect the growth of pepper seedlings except for the length of the root of the book in the treatment of sand + husk charcoal + manure media; (3) there was no interaction between leaf cutting with different compositions of growing media Key words : Black pepper, leaf cutting, composition, growing media, and cutting